2005
DOI: 10.1093/heapro/dai005
|View full text |Cite
|
Sign up to set email alerts
|

Rural women's knowledge of AIDS in the higher prevalence states of India: reproductive health and sociocultural correlates

Abstract: This study aimed to identify socio-cultural and reproductive health correlates of knowledge about AIDS among rural women using multivariate analysis of 1998-1999 National Family Health Survey (NFHS) data from two Indian states, Maharashtra and Tamil Nadu, where the urban HIV prevalence is relatively high. Analysis using multiple logistic regression was undertaken, modelling women's knowledge of AIDS, of whether the disease can be avoided, and of effective means of protection. Although 47% of all rural women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…[8] Our survey shows that main source of information about the diseases among the respondent was radio(24.53%) and television(21.43%) followed by friends and relatives(15.39%) and health worker(14.74%) whereas study done by family health international with collaboration with NCASC in 2008 shown that main source of information about disease by friends followed by radio [9] . From this study it has shown that overall knowledge regarding disease transmission was low which is slightly higher than study done in Tamil nadu, [10] India where 31% possessed correct knowledge about its transmission. The poor knowledge of HIV prevention methods among rural inhabitants could be due to poor literacy among these groups and reduced access to HIV/AIDS education material.…”
Section: Discussioncontrasting
confidence: 61%
“…[8] Our survey shows that main source of information about the diseases among the respondent was radio(24.53%) and television(21.43%) followed by friends and relatives(15.39%) and health worker(14.74%) whereas study done by family health international with collaboration with NCASC in 2008 shown that main source of information about disease by friends followed by radio [9] . From this study it has shown that overall knowledge regarding disease transmission was low which is slightly higher than study done in Tamil nadu, [10] India where 31% possessed correct knowledge about its transmission. The poor knowledge of HIV prevention methods among rural inhabitants could be due to poor literacy among these groups and reduced access to HIV/AIDS education material.…”
Section: Discussioncontrasting
confidence: 61%
“…The widespread realization that ignorance is a significant contributor to the spread of HIV/AIDS has led to a large literature in India that has tried to assess the extent of people's awareness and knowledge of the disease. This includes the studies by Izhar (1990) on data from Aligarh town and Srinagar city, Balk & Lahiri (1997) on 30,000 ever-married women in thirteen HIV-prone Indian states, Sachdev (1998) on Delhi university students, Lal et al (2000) on college students in Kerala, Hawkes & Santhiya (2002) on sexually transmitted infections in India as a whole, Kattumuri (2003) on HIV/AIDS patients in Tamil Nadu, Pallikadavath et al (2005) on rural women in Maharashtra and Tamil Nadu, and, recently, by Bloom & Griffiths (2007) on women from three culturally contrasting states of Karnataka, Kerala and Tamil Nadu. The results are varied and region-specific but the overall message from these studies is that, while knowledge of the disease in India remains quite low and grossly inadequate, the level of awareness is alarmingly low for rural women, who are particularly vulnerable to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a national HIV surveillance, the prevalence of HIV among women attending rural antenatal clinics was 0.57% compared to 0.64% in urban clinics; however, the prevalence of HIV was higher in some southern states than in rural areas. Rural residents have lesser information relating to HIV than their urban counterparts (2) and have poorer availability and access to general health services (3). Further, the quality of HIV services in rural areas is often characterized by unqualified physicians (4,5), medical practitioners refusing to care for HIV/AIDS, and poor adherence to confidentiality and other HIV-testing principles that safeguard rights of individuals and nurture trust with providers (6).…”
Section: Introductionmentioning
confidence: 99%